Analisis Bibliometrik Tren Kepemimpinan Pendidikan Berkualitas Tahun 2015 - 2024: Bibliometric Analysis of Quality Educational Leadership Trends 2015 - 2024 - Muhammad Fikri Fauzi; Datuk Muhammad; Julita Lindriany; Wahid Hasyim; Iim Iim; Sutiawati Sutiawati; Suparman Suparman (ITScience (Information Technology and Science), 2024)
This study aims to provide information related to research trends on Educational Leadership in quality education from 2015 to 2024. Article searches were conducted through a search engine with the Dimensions AI database. The PRISMA method applied in this study or Preferred Reporting Items for Systematics Review and Meta-Analysis. The study results show that Educational Leadership has been studied since 2015 with an interest of 73 articles and continues to increase until 2024; there were 244 articles recorded as of November 16, which is still possible to grow again in 2024. These results indicate that educational leadership is an aspect of interest to be studied further. The articles were selected from Dimensions AI by filtering and sorting scientific works that fall into the Quality Education category and scientific works in the form of scientific articles. The results obtained from the first filtering with the keyword